English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

(3x - 5) (2x + 3) (x - 4)= 0

2007-06-11 10:45:33 · 4 answers · asked by Big-T 2 in Science & Mathematics Mathematics

4 answers

set each binomial equal to 0

3x - 5 = 0
3x = 5
x = 5/3

2x + 3 = 0
2x = -3
x = -3/2

x - 4 = 0
x = 4

2007-06-11 10:50:15 · answer #1 · answered by      7 · 0 0

Use the zero-product property. If the product is zero, then one of your factors has to be zero.

(3x - 5) = 0 or (2x + 3) = 0 or (x - 4) = 0.

For the first one, if 3x - 5 = 0, then
3x = 5
x = 5 / 3

For the second, if 2x + 3 = 0, then
2x = -3
x = -3 / 2

Finally, if x - 4 = 0, then x = 4.

You have three solutions...
x = 5 / 3 or x = -3 / 2 or x = 4.

2007-06-11 17:51:11 · answer #2 · answered by Louise 5 · 0 0

Just set each factor =0 and solve for x.

Doing this gives 5/3, -3/2 and 4 as the roots.

2007-06-11 17:52:59 · answer #3 · answered by ironduke8159 7 · 0 0

its a simple problem involving expanding. i like how many people put homework problems on here and hope that people will answer them... glad to know where this world is heading... (straight in the tubes...)

2007-06-11 17:52:10 · answer #4 · answered by topdawg3748 2 · 0 1

fedest.com, questions and answers